5/18 a to the power 6 = 0.277a to the power 6
5-2 1/6 = 2 5/6
2/3+5/6=4/6+5/6=9/6=3/2
2 minus 5/6 = 11/6
-40x**6 / -8x**5 = 5x -48x**5 / -8x**5 = 6 -48x**4 / -8x**5 = 6x**-1 5x+6+6x**-1 OR 5x+6+6/x OR (5x**2+6x+6)/x
5/18 a to the power 6 = 0.277a to the power 6
When simplifying (6^5) over (6^3), you subtract the exponents because you are dividing two powers with the same base. So, (6^5) over (6^3) equals (6^{5-3}), which simplifies to (6^2). Therefore, the final answer is 36.
5/6 - 2/6 = 3/6 = 1/2
5/6 x 12/5 = 2
5-2 1/6 = 2 5/6
2/3 + 5/6 = 4/6 + 5/6 = 9/6 =3/2
2/3+5/6=4/6+5/6=9/6=3/2
-20/6 + 5/6 = -15/6 = -5/2 or -2 and 1/2
2 and 5/6 - 1/6 = 2 and 4/6 or 2 and 2/3
-40x**6 / -8x**5 = 5x -48x**5 / -8x**5 = 6 -48x**4 / -8x**5 = 6x**-1 5x+6+6x**-1 OR 5x+6+6/x OR (5x**2+6x+6)/x
2 minus 5/6 = 11/6
6/5 - (-2/9) 6/5 + 2/9= 64/45